The impact of a proposed training curriculum accompanied by an educational method to develop long tackles in the handball game (Journal of the College of Basic Education, 2022)
The research included five chapters. In the first chapter, the researcher touched on the importance of the research, which was evident in finding the best means used to develop and push the wheel of this game in our country forward. and get goals.In the second chapter, the researcher dealt with two main axes, the theoretical side, which included the training curriculum - its concept, tools and teaching aids, and their importance and role in physical education. .As for the third chapter, it included the research methodology and field procedures, as the researcher used A